2018
DOI: 10.1016/j.toxrep.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acute and sublethal effects of chloroquine (C18H26CIN3) on certain enzymological and histopathological biomarker responses of a freshwater fish Cyprinus carpio

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 60 publications
1
58
0
2
Order By: Relevance
“…Recently many scientific communities have deviated towards the toxicity research on pharmaceuticals (Fabbri, 2015). We have already reported the impacts of few pharmaceuticals on fresh water edible fishes (Ambili et al., 2013; Saravanan et al., 2014; Ramesh et al., 2018a,b; Renuka et al., 2018). Fish farmers use unapproved chemicals to maintain the health status of fishes by preventing and treating disease outbreaks (Nyambok and Kastner, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently many scientific communities have deviated towards the toxicity research on pharmaceuticals (Fabbri, 2015). We have already reported the impacts of few pharmaceuticals on fresh water edible fishes (Ambili et al., 2013; Saravanan et al., 2014; Ramesh et al., 2018a,b; Renuka et al., 2018). Fish farmers use unapproved chemicals to maintain the health status of fishes by preventing and treating disease outbreaks (Nyambok and Kastner, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their extensive usage and occurrence in the aquatic environment these compounds are now recognized as emerging pollutants. Even a low level of antibiotics in the water bodies could enhance microbial resistance, which results in adverse health problems to humans (Liu et al., 2018; Ramesh et al., 2018a). Amoxicillin, an aminopenicillin derivative, is a prophylactic drug belonging to β-lactams drug groups that are habitually prescribed medication against microbial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Olaitan et al (2017) found CQ in wastewater effluents in Nigeria (Olaitan et al, 2017). The general findings (Table 2) confirmed that CQ and HCQ compounds could be risky for the environment and should be classified as harmful to aquatic organisms (Ramesh et al, 2018;Zurita et al, 2005).…”
Section: Potential Environmental Impact Of Administered Drugsmentioning
confidence: 70%
“…Hydroxychloroquine and chloroquine are some of the drugs that have been used to treat COVID-19 ( Liu et al, 2020a ). These drugs have been described as persistent, bioaccumulative, and dangerous to aquatic organisms ( Ramesh et al, 2018 ), and they are considered emerging pollutants ( Daughton, 2014 ; Zurita et al, 2005 ). This is highly relevant since it is known that wastewater treatment systems do not have adequate processes for treatment these drugs, which will enter into freshwater ecosystems ( Ashfaq et al, 2017 ).…”
Section: Indirect Impact Of Covid-19 On the Environmentmentioning
confidence: 99%